The magnificent seven - Sturges, John, 1910-1992; Roberts, William S., 1913-1997; Brynner, Yul; Wallach, Eli, 1915-; McQueen, Steve, 1930-1980; Bronson, Charles, 1920-2003; Vaughn, Robert, 1932-; Dexter, Brad, 1917-2002; Coburn, James; Buchholz, Horst, 1933-2003; Lang, Charles B; Webster, Ferris, 1912-1989; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2006)
Seven gunmen are hired by a small village to protect them from the bandits destroying their town
Disc 1. Feature film -- Disc 2. Special features
"Based on the Japanese film "Seven Samurai, " Toho Company, Ltd."
Originally produced as a motion picture in 1960
Special features include: Disc 1: audio commentary with actors James Coburn, Eli Wallach; audio commentary with film historian Sir Christopher Frayling ; Disc 2: "Guns for hire - the making-of 'The magnificent seven'" documentary; "Christopher Frayling on 'The magnificent seven'" featurette; "Elmer Bernstein and 'The magnificent seven'" featurette; "The linen book: lost images from 'The magnificent seven'" featurette; photo gallery
Cinematography, Charles Lang, Jr.; editor, Ferris Webster; music, Elmer Bernstein
Yul Brynner, Eli Wallach, Steve McQueen, Charles Bronson, Robet Vaughn, Brad Dexter, James Coburn, Horst Buchholz
Not rated
Keywords: Outlaws -- Drama; Vigilantes -- Drama; Peasants -- Mexico -- Drama; Feature films; Fiction films; Western films; Video recordings for the hearing impaired; DVD-Video discs; Video recordings